Antibacterial and Phytochemical Screening of Root Extracts of Senna singuaena - Ethiopia, Mebrahtom Gebrelibanos (International Journal of Pharmaceutical & Biological Archive, 2015)
Antibacterial and Phytochemical Screening of Root Extracts of Senna singuaena